Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 38896 by math khazana by abdo last updated on 01/Jul/18

let A_n = ∫_0 ^n    ((x[x])/(1+x^2 )) dx  1) calculate A_n   2) find lim_(n→+∞)  A_n

letAn=0nx[x]1+x2dx1)calculateAn2)findlimn+An

Commented by math khazana by abdo last updated on 01/Jul/18

1) we have A_n = Σ_(k=0) ^(n−1)  ∫_k ^(k+1)    ((kx)/(1+x^2 ))dx  =Σ_(k=0) ^(n−1)  k ∫_k ^(k+1)   ((xdx)/(1+x^2 ))  =Σ_(k=0) ^(n−1)  (k/2)(ln(1+(k+1)^2 ) −ln(1+k^2 ))  =Σ_(k=0) ^(n−1)    (k/2)ln{((1 +k^2  +2k+1)/(k^2  +1))}  =Σ_(k=0) ^(n−1)   (k/2)ln{  ((k^2  +2k+2)/(k^2  +1))}    2) ln{ ((k^2  +2k +2)/(k^2  +1))}=ln{  ((k^2  +1 +2k+1)/(k^2  +1))}  =ln( 1+ ((2k+1)/(k^2  +1))) but  ln^′ (1+x) =(1/(1+x)) =1−x +o(x^2 ) ⇒  ln(1+x) =x −(x^2 /2) +o(x^3 ) ⇒  x−(x^2 /2) ≤ ln(1+x)≤x  ⇒  ((2k+1)/(k^2  +1))  −(1/2)(((2k+1)^2 )/((k^2 +1)^2 )) ≤ ln(1+((2k+1)/(k^2  +1)))≤ ((2k+1)/(k^2  +1)) ⇒  (k/2){ ((2k+1)/(k^2  +1)) −(1/2) (((2k+1)^2 )/((k^2  +1)^2 ))}≤ (k/2)ln(1+((2k+1)/(k^2  +1)))  ≤ (k/2) ((2k+1)/(k^2  +1)) ⇒  A_n  ≥ Σ_(k=1) ^(n−1)   ((k(2k+1))/(2k^2  +2)) −Σ_(k=1) ^(n−1)  (k/4) (((2k+1)^2 )/((k^2  +1)^2 )) →+∞  (n→+∞) so lim_(n→+∞)  A_n =+∞.

1)wehaveAn=k=0n1kk+1kx1+x2dx=k=0n1kkk+1xdx1+x2=k=0n1k2(ln(1+(k+1)2)ln(1+k2))=k=0n1k2ln{1+k2+2k+1k2+1}=k=0n1k2ln{k2+2k+2k2+1}2)ln{k2+2k+2k2+1}=ln{k2+1+2k+1k2+1}=ln(1+2k+1k2+1)butln(1+x)=11+x=1x+o(x2)ln(1+x)=xx22+o(x3)xx22ln(1+x)x2k+1k2+112(2k+1)2(k2+1)2ln(1+2k+1k2+1)2k+1k2+1k2{2k+1k2+112(2k+1)2(k2+1)2}k2ln(1+2k+1k2+1)k22k+1k2+1Ank=1n1k(2k+1)2k2+2k=1n1k4(2k+1)2(k2+1)2+(n+)solimn+An=+.

Commented by math khazana by abdo last updated on 01/Jul/18

2) another method  we have 0≤x≤n ⇒  0≤x^2 ≤n^2  ⇒ 1≤1+x^2  ≤ 1+n^2  ⇒ (1/(1+x^2 )) ≥ (1/(1+n^2 ))  ⇒ A_n ≥ (1/(1+n^2 )) ∫_0 ^n  x[x]dx but  ∫_0 ^n  x[x]dx =Σ_(k=0) ^(n−1)  ∫_k ^(k+1)  kx dx  =Σ_(k=0) ^(n−1) k { (((k+1)^2 )/2) −(k^2 /2)}  =Σ_(k=0) ^(n−1)  k { ((k^2  +2k +1−k^2 )/2)}  =Σ_(k=0) ^(n−1)  k ((2k+1)/2)  =Σ_(k=0) ^(n−1)  k^2   +(1/2) Σ_(k=0) ^(n−1)  k  = (((n−1)(n−1+1)(2(n−1)+1))/6)  +(1/2) (((n−1)n)/2)  =((n(n−1)(2n−1))/6) +(1/4)(n^2  −n) ⇒  A_n  ≥ (1/(n^2  +1)){  ((n(n−1)(2n−1))/6) +(1/4)(n^2 −n)}→+∞  (n→+∞)

2)anothermethodwehave0xn0x2n211+x21+n211+x211+n2An11+n20nx[x]dxbut0nx[x]dx=k=0n1kk+1kxdx=k=0n1k{(k+1)22k22}=k=0n1k{k2+2k+1k22}=k=0n1k2k+12=k=0n1k2+12k=0n1k=(n1)(n1+1)(2(n1)+1)6+12(n1)n2=n(n1)(2n1)6+14(n2n)An1n2+1{n(n1)(2n1)6+14(n2n)}+(n+)

Answered by tanmay.chaudhury50@gmail.com last updated on 01/Jul/18

A_n =∫_0 ^1 ((x×0)/(1+x^2 ))dx+∫_1 ^2 ((x×1)/(1+x^2 ))dx+∫_2 ^3 ((x×2)/(1+x^2 ))+    ∫_(n−1) ^n ((x×(n−1))/(1+x^2 ))dx  =(1/2)×1∫_1 ^2 ((2x)/(1+x^2 ))dx+(1/2)×2∫_2 ^3 ((2x)/(1+x^2 ))dx+(1/2)×3∫_3 ^4 ((2x)/(1+x^2 ))  (1/2)×4∫_4 ^5 ((2x)/(1+x^2 ))+...+(1/2)×(n−1)∫_(n−1) ^n ((2x)/(1+x^2 ))dx  =(1/2){1×∣ln(1+x^2 )∣_1 ^2 +2×∣ln(1+x^2 )∣_2 ^3 +..+  (n−1)∣ln(1+x^2 )∣_(n−1) ^n }  =(1/2)[1×(ln5−ln2)+2×(ln10−ln5)+    +...+(n−1){ln(1+n^2 )−ln(1+(n−1)^2 }]  =(1/2)ln{((5/2))^1 ×(((10)/5))^2 ×...×(((1+n^2 )/(1+(n−1)^2 )))^(n−1) }

An=01x×01+x2dx+12x×11+x2dx+23x×21+x2+n1nx×(n1)1+x2dx=12×1122x1+x2dx+12×2232x1+x2dx+12×3342x1+x212×4452x1+x2+...+12×(n1)n1n2x1+x2dx=12{1×ln(1+x2)12+2×ln(1+x2)23+..+(n1)ln(1+x2)n1n}=12[1×(ln5ln2)+2×(ln10ln5)++...+(n1){ln(1+n2)ln(1+(n1)2}]=12ln{(52)1×(105)2×...×(1+n21+(n1)2)n1}

Terms of Service

Privacy Policy

Contact: info@tinkutara.com